Analisis Pengaruh Pendidikan Dan Pelatihan, Motivasi Dan Penempatan Kerja Terhadap Kinerja Karyawan Pada PT. Indonesia Power Pltu Pangkalan Susu Omu Unit 1-2 - Henny Pratiwi; Muhammad Ilham Riyadh; Isnirobit Nasution; Fahmi Sulaiman (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
This study aims (a) To determine and analyze the effect of education and training partially on employee performance (b) To determine and analyze the effect of work motivation partially on employee performance (c) To determine and analyze the effect of job placement partially on employee performance ( d) To determine and analyze the effect of education and training, work motivation and work placement simultaneously on employee performance. The problem to be investigated is that the performance is less than optimal because there are still employees who are not optimal in carrying out their duties as indicated by (a) There are some employees who do not know the work process of the new system that has just been adopted by the company. (b) There are still found employees who have not mastered the technology used by the company (c) Work motivation of employees who are not good so that employee performance decreases because employees are too often in and out of the workspace for no reason and the level of attendance is minimal. (d) There are still employees who complain about work placements that are not in accordance with applicable regulations. (e) The existing work placement system in the company is still subjective. The research was conducted at PT. Indonesia Power PLTU Pangkalan Susu OMU Unit 1-2. This study used a questionnaire as a research instrument and distributed to 35 employees. From the results of data processing, obtained a significance value of 0.001 which is smaller than 0.05. From this analysis, Ho is rejected, meaning that there are simultaneously independent variables affecting the dependent variable. To improve employee performance, education and training, motivation and work placement must also be increased. The value of the Adjusted R Square in the table above is 0.304 or 30.4%. This condition explains that 30.4% of the variables are Education and Training, Work Motivation and Work Placement. The remaining 69.6% is influenced by other variables not examined in this study. This means that from several factors supporting Education and Training, Work Motivation and Work Placement that affect employee performance the most is 30.4%